On the Response of Protons to Dynamical Reconfigurations of Mercury's Magnetosphere - D. Delcourt; L. Z. Hadid; S. Aizawa (Geophysical Research Letters)
Abstract We examine the dynamics of protons during tail‐like to dipole‐like reconfigurations of Mercury's magnetosphere. Such reconfigurations that frequently occur in the highly dynamical Hermean environment are accompanied by induced electric fields leading to short‐lived convection enhancements. Using test particle calculations, we show that, under the effect of such induced electric fields, protons may be subjected to prominent energization while being injected into the inner magnetosphere. We demonstrate that this energization occurs in a nonadiabatic manner and can reach several tens of keV, possibly leading to particle trapping around the planet. Recent observations from BepiColombo during Mercury's third flyby provide evidences of energetic protons drifting in the vicinity of the planet. The present impulsive energization process is a possible mechanism for the build‐up of such populations.